Design and Optimization of Rivaroxaban Lipid Solid Dispersion for Dissolution Enhancement using Statistical Experimental Design - Ganesh, M (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The purpose of the present study was to understand the effect of formulation variables of lipid solid dispersion on the dissolution of a model drug, rivaroxaban. Method: A three-factor, three-level Box–Behnken design was used to explore the main and interaction effect of several independent formulation variables including the amount of Gelucire 48/16 (X1), Compitrol HD5 ATO (X2), and Labrasol (X3). Particle size (Y1) and dissolution percentage of rivaroxaban (Y2) were the dependent variables. Statistical Analysis: A mathematical relationship was obtained to explain the effect of all factors and their colinearities on the dissolution of rivaroxaban. Results: A formulation optimization was then performed to maximize dissolution percentage of rivaroxaban (Y2). The optimized formulation was predicted to dissolution 62.4% of rivaroxaban at 5 min, when X1, X2, and X3 values were 20.0, 30.0, and 2.0 mg, respectively. Conclusion: In conclusion, the Box–Behnken experimental design allowed us to understand the effect of formulation variables on the dissolution of rivaroxaban from lipid solid dispersion, and optimize the formulation to obtain drug dissolution.